2021
DOI: 10.3390/cancers13246302
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Palmitoyltransferase 1 Regulates Prostate Cancer Growth under Hypoxia

Abstract: Hypoxia and hypoxia-related biomarkers are the major determinants of prostate cancer (PCa) aggressiveness. Therefore, a better understanding of molecular players involved in PCa cell survival under hypoxia could offer novel therapeutic targets. We previously reported a central role of mitochondrial protein carnitine palmitoyltransferase (CPT1A) in PCa progression, but its role in regulating PCa survival under hypoxia remains unknown. Here, we employed PCa cells (22Rv1 and MDA-PCa-2b) with knockdown or overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Especially PPARG was shown to be activated under hypoxic conditions in correlation with HIF1A in lung cancer and hepatocellular carcinoma [ 76 , 77 ]. It regulated the differentially expressed gene carnitine palmitoyltransferase 1A (CPT1A) and its homolog CPT1B, shown to regulate prostate cancer growth under hypoxic conditions [ 78 ]. While this module does not show strong dysregulation in the three analyzed cancer types, it contained genes and interactions highly relevant in reaction to hypoxia, as demonstrated in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Especially PPARG was shown to be activated under hypoxic conditions in correlation with HIF1A in lung cancer and hepatocellular carcinoma [ 76 , 77 ]. It regulated the differentially expressed gene carnitine palmitoyltransferase 1A (CPT1A) and its homolog CPT1B, shown to regulate prostate cancer growth under hypoxic conditions [ 78 ]. While this module does not show strong dysregulation in the three analyzed cancer types, it contained genes and interactions highly relevant in reaction to hypoxia, as demonstrated in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal CPT1A expression was associated with the poor OS of AML (43), ovarian cancer (44), and glioblastoma stem cells (45). Leslimar et al reported that CPT1A could regulate prostate cancer survival in hypoxic conditions and promote aggressiveness (46). IDH3A, isocitrate dehydrogenases 3 Catalytic Subunit Alpha, is the key part of isocitrate dehydrogenases, catalyzing the oxidative decarboxylation of isocitrate to a-ketoglutarate in citrate cycle (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues were processed, and 5 µm formalin-fixed and paraffin-embedded (FFPE) sections were analyzed for CD63 expression by processing and immunohistochemistry (IHC) as described by us previously [ 39 ] . CD63 primary antibody was purchased from ThermoFisher (Waltham, MA) and detection system (ImmPRESS-AP horse anti-rabbit IgG polymer detection kit) with secondary antibody from Vector laboratories (Burlingame, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration and size distribution of the EVs were analyzed using Nanosight NS300 (Malvern Instruments, UK) as described earlier [38] .…”
Section: Nanoparticle Tracking Analysesmentioning
confidence: 99%
See 1 more Smart Citation